Biogeography and Diversity of Lobophyllia, an Ornamental Coral Traded in the Coral Triangle. (April 2019) - Yusuf, S; Jompa, J; Ahmad, M; Umar, W; Limmon, G V
Abstract: The coral reefs in the Coral Triangle (CT) are the most biodiverse in the world, but are exposed to growing anthropogenic and natural threats. The collection of corals for export in the marine ornamental trade has been going on for almost 40 years in Indonesia, but recently (in early 2018) it was stopped by the government under an indefinite moratorium. Lobophyllia is one of the more intensively exploited corals, with a total quota of 2500 pieces/year. Within the Indonesian CT area (ICTA), very little is known regarding the diversity, population status, and distribution of Lobophyllia, at either unexploited or intensively exploited sites. Therefore, this study aimed to determine the species diversity, population status, and distribution of coral Lobophyllia at several Indonesian coral reef locations. Primary and secondary data were collected on the coral Lobophyllia, both at sites exploited by ornamental coral collectors and at unexploited sites. Primary data were obtained from coral reef surveys that took place under various programs over the period 1998-2017 at 25 locations in the ICTA. Lobophyllia was found to be widespread on Indonesian coral reefs. Although 9 species were recorded, only brightly coloured colonies measuring 10-25 cm were exploited. Indonesia classified Lobophyllia corymbosa and Lobophyllia spp. (multispecies) as export trade target commodities. As a result, some species of Lobophyllia targeted as ornamental corals have become very rare at exploited sites compared to on unexploited reefs. If coral exploitation continues to be halted (moratorium), it is expected that depleted Lobophyllia populations, especially at exploited locations, could recover naturally.